2018
DOI: 10.1186/s13148-018-0579-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DNA methylation is related to increased expression of miR-21 and miR-146b in papillary thyroid carcinoma

Abstract: BackgroundDNA methylation in miRNA genes has been reported as a mechanism that may cause dysregulation of mature miRNAs and consequently impact the gene expression. This mechanism is largely unstudied in papillary thyroid carcinomas (PTC).MethodsTo identify differentially methylated miRNA-encoding genes, we performed global methylation analysis (Illumina 450 K), integrative analysis (TCGA database), data confirmation (pyrosequencing and RT-qPCR), and functional assays.ResultsMethylation analysis revealed 27 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…However, NNK-induced DNA methylation can, at the same time, modulate miRNA levels by regulating MMR gene expression. Hypo-or hyper-methylation of miRNA was considered to represent a new level of complexity in gene regulation in human cancers [81], suggesting miR-21 or miR-155 promoter hypo-methylation [81][82][83][84] and miR-422a hyper-methylation, as previously reported for miR-373 [81,85], as potential epigenetic modifications caused by tobacco carcinogenic effects on MMR. On the other hand, alkylating agents, such as NNK can also directly or after biological activation react and form covalent bonds with nucleophilic centers found in DNA and RNA and proteins [86], supporting possible direct interference of NNK with levels of miRNAs, thereby causing their deregulation [48,49,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, NNK-induced DNA methylation can, at the same time, modulate miRNA levels by regulating MMR gene expression. Hypo-or hyper-methylation of miRNA was considered to represent a new level of complexity in gene regulation in human cancers [81], suggesting miR-21 or miR-155 promoter hypo-methylation [81][82][83][84] and miR-422a hyper-methylation, as previously reported for miR-373 [81,85], as potential epigenetic modifications caused by tobacco carcinogenic effects on MMR. On the other hand, alkylating agents, such as NNK can also directly or after biological activation react and form covalent bonds with nucleophilic centers found in DNA and RNA and proteins [86], supporting possible direct interference of NNK with levels of miRNAs, thereby causing their deregulation [48,49,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 64%
“…Recently, there has been increasing interest in assessing the predictive value of a defective MMR mechanism in various types of cancer, including lung and head and neck cancer [91,92]. In addition, recent studies strongly support that MMR status can alter the efficacy of target immunotherapy, and the identification of MMR status prior to initiation of treatment may be a useful approach [36,83]. The fact that NNK, in addition to its mutagenic effect, which is manifested by inducing DNA defects, can simultaneously suppress the DNA repair mechanism and promote cellular antiapoptosis, supports its carcinogenic potency.…”
Section: Discussionmentioning
confidence: 99%
“…17 Alteration of DNA methylation level in miRNA promoter directly results in the change of its expression level. 18 Vera et al 19 reported that the increase of miR-7 methylation level could act as a potential clinical epigenetic biomarker for the identification of ovarian cancer patients with poor response to platinum-derived therapy. Undoubtedly, there is a crucial role for DNA methylation in many types of diseases, but its role in aged myocardial I/R injury is still poorly understood.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
“…The expression of multiple miRNAs can be altered by epigenetic mechanisms leading to the misregulation of target genes and causing cancer. For instance, the upregulation of miR-21, observed in several cancers (Table 3), can be attributed to a loss of DNA methylation in its promoter [267]. DNA hypomethylation increases the expression of miR-21 and miR-146b in papillary thyroid carcinoma [267].…”
Section: Discussionmentioning
confidence: 99%